Control of Shape and Size in Iron Fluoride Porous Sub-Microspheres: Consequences for Steric Hindrance Interaction - Song, Weibing; Lu, Hongyu; Zhao, Wenlong; Cao, Xiaofei; Yan, Lei; Zhao, Jingxin; Li, Neng; Tang, Yuxin; Hu, Jun (Frontiers in Nanotechnology, 2021)
Iron-based fluorides are promising for advanced sodium-free batteries cathode due to the large theoretical capacity. However, the rational structure control on the iron-based fluorides towards high performance batteries is still challenging. To this end, controllable porous structure on FeF3·0.33H2O sub-microspheres is achieved by a polyethylene glycol (PEG)-assisted hydrothermal method via adjusting the volume of PEG-400. Experimental and molecules dynamic results verify that the formation of small amethyst-like sub-microspheres is mainly ascribed to the steric hindrance reaction of PEG-400, which makes it difficult for F- to combine with Fe3+ to form coordination bonds, and partially hinders the nucleation and growth of FeF3·0.33H2O nanospheres. As a sodium-free battery cathode, the FeF3·0.33H2O sub-microspheres with porous structure and smaller particle size exhibit excellent electrochemical performance in regard to cycle capacity and rate capability (a remaining capacity of 328 mAh-1 and up to 95.3% retention rate when backs to 0.1 C after 60 cycles).